Go-Green Introduction Program for Children with Special Needs - Andi Anggi Adei Putri (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
The Green Introduction Program for Children with Special Needs is a unique and innovative educational program that promotes environmental sustainability and conservation while enhancing the holistic development of special needs children. This program involves hands-on experiences in nature and is designed to address the cognitive, physical, and emotional needs of special needs children. However, challenges such as limited resources, limited accessibility, inadequate teacher training, and individual differences must be addressed for the program to be successful and sustainable. Future directions for the program include expanding accessibility, providing teacher training, individualizing programming, and conducting ongoing program evaluation. The Green Introduction Program for Children with Special Needs has the potential to provide a valuable educational experience for special needs children while promoting environmental sustainability and conservation.